PENGARUH PRODUKTIVITAS QUAY CRANE TWINLIFT TERHADAP WAKTU SANDAR KAPAL DI DERMAGA UTARA - Muhammad Rifni; Widya Eka Purnamasari (Institut Transportasi dan Logistik Trisakti, 2014)
There is a significance correlation between the productivity of Quay Crane Twin lift to the time used for shipping dock at the north pier. It could happen due to suffice and qualified human resources, facilities and equipments provided by the company. Based on the analysis of correlation, PT. Jakarta International Container Terminal in 2008-2010, performs r = 0.376 which means that there is a relationship between variables X and Y. The determinant coefficient test showed 14.14% means that the contribution of the productivity of quay crane twinlift (X) to the time used for shipping docked (Y) is suffice.